Ion Selectivity and Stability Enhancement of SPEEK/Lignin Membrane for Vanadium Redox Flow Battery: The Degree of Sulfonation Effect - Ye, Jiaye; Lou, Xuechun; Wu, Chun; Wu, Sujuan; Ding, Mei; Sun, Lidong; Jia, Chuankun (Frontiers in Chemistry, 2018)
A membrane of high ion selectivity, high stability and low cost is desirable for vanadium redox flow battery (VRB). In this study, a composite membrane is formed by blending the sulfonated poly (ether ether ketone) with lignin (SPEEK/lignin), and optimized by tailoring the degree of sulfonation. The incorporation of lignin into the SPEEK matrix provides more proton transport pathway and meanwhile adjusts the water channel to repulse vanadium ions. The VRB cells assembled with the composite membranes exhibit high coulombic efficiency (~99.27%) and impressive energy efficiency (~82.75%). The cells maintain a discharge capacity of ~95 % after 100 cycles and ~85% after 200 cycles at 120 mA cm-2, much higher than the commercial Nafion 212. The SPEEK/lignin composite membranes are promising for application in VRB system.